CeBr3 scintillators for 4He prompt gamma spectroscopy: results from a Monte Carlo optimization study - Dal Bello, Riccardo; Magalhães Martins, Paulo; Seco, Joao (Medical physics, 2018)
Purpose Range uncertainties limit the potential of charged particle therapy. In vivo and online range verification techniques could increase the confidence in the dose delivery distribution and lead to more conformal treatments. Prompt gamma imaging and prompt gamma spectroscopy (PGS) have been demonstrated for such a purpose. The successful application of these techniques requires the development of a dedicated detector system optimized to the radiation energy ranges and the intensity. In this work, we investigated a detector system based on CeBr3 crystals capable of performing spectroscopy of the prompt gamma radiation induced by 4He beams. Methods We performed Monte Carlo simulations to optimize the detector system. The study was carried out both with the Geant4 toolkit and the FLUKA package. The simulated system consisted of a primary crystal for spectroscopy and secondary crystals for noise reduction in anticoincidence (AC). For comparison purposes, we considered a configuration without AC crystals. We first defined the dimensions of the primary cerium bromide (CeBr3) crystal and the secondary bismuth germanate (BGO) or CeBr3 crystals. We then evaluated their detection performance for monoenergetic gamma radiation up to 7 MeV in such way that the probability of the photo-peak detection was maximized in comparison to the number of escape peak and Compton events. We simulated realistic prompt gamma radiation spectra induced by 4He beams on homogeneous targets (water, graphite, and aluminum) and on implants (water with an aluminum insert). Finally, we tested the performances of the optimized systems in the detection of the realistic gamma spectra. The quantitative analysis was accomplished by comparing the signal-to-noise ratio between the different configurations and the ability to resolve the discrete reactions. Results We present the optimized dimensions for the primary CeBr3 crystals with and without AC shielding. The specific values are given over a wide range of crystal volumes. The results show an optimal primary CeBr3 crystal with an approximately diameter to length ratio of 1 without AC shielding and 0.5 with AC shielding. The secondary BGO and CeBr3 should have a transverse dimension of 3 and 4.56 cm, respectively. The analysis of the prompt gamma spectra from 4He beams highlighted the presence of specific discrete reactions not observed in 1H studies, for example, 12C transition 0+ (7.65 MeV) ?2+ (4.44 MeV). This reaction is responsible for the generation of the 3.21 MeV prompt gamma peak. The optimized primary crystal provides a significant increase in the signal-to-noise ratio together with an improved resolution of the discrete gamma lines, especially in the high-energy region. The detection configuration with an optimized anticoincidence crystal improved the signal-to-noise ratio up to a factor of 3.5. Conclusions This work provides the optimal geometry for primary and secondary crystals to be used in range verification through PGS. The simulations show that such a PGS system may allow for the simultaneous detection of the discrete lines from a thin metal implant within a water phantom.